Sur les mouvements dans l’espace des éléments hyperplans - Urbonas, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Урбонас. О движениях в пространстве гиперплоскостных элементов A. Urbonas. Apie judesius hiperplokštuminių elementų erdvėje